The PEMENUHAN HAK PEREMPUAN DAN ANAK DALAM PENYELESAIAN SENGKETA HARTA BERSAMA PASCA PERCERAIAN (Pada Putusan Perkara No 5034/Pdt.G/2022/Pa.Grt Di Pengadilan Agama Kelas I A Garut Bulan Januari Tahun 2023): English - Habib Mumtaz JR Mumtaz; Yahya Saepul Uyun; Ade Jamarudin; Imam Sucipto (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2023)
The problem is how to resolve disputes over post-divorce women's rights through the courts, of course there are pros and cons. The point of view studied is KHI (Islamic Law Collection) Articles 105 and 156 as well as Law No. 1 of 1974 which was changed to Law No. 16 of 2019 and Law No. 23 of 2002 concerning the rights of women and children by analyzing the report on the divorce suit decision as of January in 2023 by the Garut Religious Court. The analytical method used is empirical with a qualitative approach. Primary and secondary sources as well as observations are used at all times. In conclusion, the implementation of court decisions is not all carried out effectively and as expected, this is because the level of husband's economic ability is uncertain and even dominated by absenteeism in solving problems. the consequences will be the same, namely it will not be realized. From the research, it is known that 78% have carried out the decisions set by the Court with the results of the Verstek Decision, but there are some who have not carried out in accordance with the Court's provisions, due to economic factors and the current situation after the pandemic. And one of the decisions in the case with Number. 5034/Pdt.G/2022/PA.Grt with the result of the judge's consideration decision, which is granted in part and Custody of one of the children is with the Plaintiff but for joint assets it is still in a temporary decision or under review.